Gene name errors are widespread in the scientific literature - Ziemann, Mark; Eren, Yotam; El-Osta, Assam (Genome Biology, 2016)
The spreadsheet software Microsoft Excel, when used with default settings, is known to convert gene names to dates and floating-point numbers. A programmatic scan of leading genomics journals reveals that approximately one-fifth of papers with supplementary Excel gene lists contain erroneous gene name conversions.